(untitled) (INNOVATIVE ECONOMY, 2025)
Lishchynskyy I.O., Lyzun M.V. CIRCULAR CLUSTERS IN CENTRAL AND EASTERN EUROPE: A CATALYST FOR STIMULATING SUSTAINABLE DEVELOPMENT Purpose. The aim of this paper is to analyse the activities of circular clusters in Central and Eastern Europe as a powerful tool for promoting the sustainability of local economies in conditions of resource scarcity and external uncertainties. Methodology of research. The study employed the following methods: the abstract and logical method to synthesize information from various sources, develop a comprehensive understanding of the research issues, and form theoretical conclusions and generalizations related to the paradigm of sustainable development and the role of circular clusters; analysis and synthesis to describe the activities of circular clusters and develop recommendations for their advancement; and graphical methods to visualize the research findings. Findings. Although circular cluster practices in Central and Eastern Europe are still in the early stages, they have significant potential to reduce dependence on traditional resource-intensive industries, such as metallurgy and agriculture. The study found that the primary principles driving their activity are the collaboration of national and local stakeholders to enhance resource efficiency, the implementation of material reuse principles, and increased cooperation across various economic sectors. The article analysed the activities of circular clusters in Central and Eastern European countries, focusing on waste management, recycling, and eco-design. It was demonstrated that, at the current stage, existing circular clusters in the region function more as national alliances of like-minded entities than as traditional specialized territorial associations. Originality. The article substantiates the necessity and specifics of developing circular clusters in Central and Eastern Europe and defines their role in reducing dependency on traditional resource-intensive sectors and enhancing the region’s economic resilience. Practical value. The results of the conducted research testify that the development of circular clusters in Central and Eastern Europe holds substantial potential for the region’s sustainable growth. Integrating these clusters into the pan-European network, supported by the EU, will promote the development of environmentally sustainable business models and improve economic resilience. Moreover, the results of the study could provide a basis for addressing infrastructure provision, regulatory barriers, and raising public awareness of the benefits of the circular economy, thus supporting the successful functioning of circular clusters. Key words: sustainable development, circular economy, circular clusters, European integration, infrastructure, industry, waste management.